2021
DOI: 10.1016/j.ajem.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cardiovascular disease and acute cardiac injury on fatal COVID-19: a meta-analysis

Abstract: Background With the continuance of the global COVID-19 pandemic, cardiovascular disease (CVD) and cardiac injury have been suggested to be risk factors for severe COVID-19. Objective The aim is to evaluate the mortality risks associated with CVD and cardiac injury among hospitalized COVID-19 patients, especially in subgroups of populations in different countries. Methods A comprehensive systematic literature search was performed using 9 datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 65 publications
0
14
0
3
Order By: Relevance
“…It was found that an acute cardiac injury occurred in a significant number of COVID19 patients, leading to increased admission to the intensive care unit and higher mortality (Momtazmanesh et al, 2020;Vakhshoori et al, 2020b;Li et al, 2020a). Recently, Long et al (Long et al, 2021) evaluated by meta-analysis the mortality risks associated with cardiovascular disease (CVD) and cardiac injury in hospitalized COVID19 patients in populations from four different countries and found that hospitalized COVID19 patients with cardiovascular events were at a higher risk of fatal outcomes than those without CVD (Shoar et al, 2020;Long et al, 2021).…”
Section: Cardiac Injurymentioning
confidence: 99%
“…It was found that an acute cardiac injury occurred in a significant number of COVID19 patients, leading to increased admission to the intensive care unit and higher mortality (Momtazmanesh et al, 2020;Vakhshoori et al, 2020b;Li et al, 2020a). Recently, Long et al (Long et al, 2021) evaluated by meta-analysis the mortality risks associated with cardiovascular disease (CVD) and cardiac injury in hospitalized COVID19 patients in populations from four different countries and found that hospitalized COVID19 patients with cardiovascular events were at a higher risk of fatal outcomes than those without CVD (Shoar et al, 2020;Long et al, 2021).…”
Section: Cardiac Injurymentioning
confidence: 99%
“…The majority of studies (46 studies) reported the impact of CI on mortality (Table 1) [5,12,15,17,18,20,[22][23][24]29,[31][32][33]35,39,40,[42][43][44][45][46][47][48][49][50][51][52][53][56][57][58][59][60][61][62][63][64][65][66][67]70,73,74,[76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…Checking troponin levels was useful among older individuals regardless of their cardiac-related comorbidities [17]. Increased length of hospital stay (median days, 5 [3][4][5][6][7][8][9] vs. 4 [2][3][4][5][6][7]) and ICU admission (46.2% vs. 31.4%) occurred more frequently in the myocardial-injury group. Based on these findings, for every 100 hospitalized patients, patients with higher troponin levels would be anticipated to result in 15 additional ICU admissions until hospital discharge with an overall increased length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stay, ICU admission rates, and in-hospital mortality were higher among myocardial-injury patients than no-myocardial-injury patients according to the univariate analyses (median length of stay, 5 (3)(4)(5)(6)(7)(8)(9) days for the myocardial-injury group and 4 (2-7) days for the no-myocardial-injury group; ICU admission, 46.2% vs. 31.4%; mortality, 22.8% vs. 11.6%; Table 3). The survival analysis showed a clear difference in the Kaplan-Meier plot based on the univariate analysis (Figure 1 shows the survival analysis results stratified by myocardial injury based on the univariate analysis).…”
Section: Outcome Measuresmentioning
confidence: 97%
See 1 more Smart Citation